Paket Pembelajaran Fiqih Kelas VII dengan Menggunakan Model Dick dan Carey di Madrasah Tsanawiyah NW Pengkelak Mas - Hanafi; I Nyoman Sudana Degeng; Anselmus JE Toenlioe (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
The development of teaching materials is an effort to facilitate learning and improve the quality of instruction carried out by students both inside and outside the school environment. In practice, learning can be effectively implemented when using specially developed teaching materials that take into account the characteristics of the users. The development model used in this study is the Dick, Carey, and Carey model. Based on the results of data analysis from each trial conducted by the developer, it can be concluded that the analysis results obtained from content experts, media experts, design experts, individual trials, small group trials, and field trials indicate that the developed learning package is highly suitable for use in the learning process.